Experimental optimization and analysis of intake and exhaust pipeline for small engine motorcycle. - Shih, Chien-Jong (Journal of Applied Science and Engineering)
In this paper, the investigation on the effects of intake and exhaust pipeline of a 125 cc small engine motorcycle is presented. The formal design of experiment (DOE) has been utilized to examine the significances of related parameters of pipelines. Four performance functions including the engine torque, fuel consumption, emission of CO and HC have been constructed by response surface methodology (RSM). The weighting strategy of four-objective optimization in six design cases was employed for analysis, comparison, and discussion. After some experimental investigations which provides some useful guidelines for intake and exhaust pipeline design. The proposed integrated process positively enhances the engine torque of overall speed and reduces the fuel consumption. The torque of low range speed can be particularly increased with the methodology presented in this paper. No clear evidence supports the polluted emission can be effectively deducted by modifying the intake pipeline system.